2011
DOI: 10.2174/1874241601104010034
|View full text |Cite
|
Sign up to set email alerts
|

The Oxidative Stress of Hyperhomocysteinemia Results from Reduced Bioavailability of Sulfur-Containing Reductants

Abstract: Vegetarian subjects consuming subnormal amounts of methionine (Met) are characterized by subclinical protein malnutrition causing reduction in size of their lean body mass (LBM) best identified by the serial measurement of plasma transthyretin (TTR). As a result, the transsulfuration pathway is depressed at cystathionine--synthase (C S) level triggering the upstream sequestration of homocysteine (Hcy) in biological fluids and promoting its conversion to Met. Maintenance of beneficial Met homeostasis is counter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 147 publications
0
6
0
Order By: Relevance
“…Both the highest and lowest dietary Met levels exerted similar effects on many parameters (concentrations of vitamin C and LOOH, activity of CAT and GPx, FRAP values). Ingenbleek (2011) demonstrated that dietary Met deficiency induced oxidative stress in vegetarian subjects consuming deficient amounts of Met. In another experiment (Castellano et al, 2015), a decrease in blood FRAP values was noted in piglets fed Met-deficient diets.…”
Section: Discussionmentioning
confidence: 99%
“…Both the highest and lowest dietary Met levels exerted similar effects on many parameters (concentrations of vitamin C and LOOH, activity of CAT and GPx, FRAP values). Ingenbleek (2011) demonstrated that dietary Met deficiency induced oxidative stress in vegetarian subjects consuming deficient amounts of Met. In another experiment (Castellano et al, 2015), a decrease in blood FRAP values was noted in piglets fed Met-deficient diets.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased enzymatic and nonenzymatic production 39,165,166,293 Increased production cancelled out by tissue overconsumption 79 Abbreviations: CRP, C-reactive protein; LBM, lean body mass; S, sulfur; SAA, S-containing amino acids; SO4 2-, sulfate. a LBM shrinking may be the result of either dysmaturation of body protein tissues as an effect of protracted dietary SAA deprivation or of cytokine-induced depletion of body stores.…”
Section: Status Of Cys-gsh-h2s Reducing Moleculesmentioning
confidence: 99%
“…Homocysteine metabolism involves two pathways, that is, trans-sulfuration pathway and re-methylation pathway [1]. Homocysteine metabolism involves two pathways, that is, trans-sulfuration pathway and re-methylation pathway [1].…”
Section: Introductionmentioning
confidence: 99%
“…Homocysteine is a nonproteogenic sulfurated amino acid derived from ingested methionine found in cheese, eggs, fish, meat, and poultry. Homocysteine metabolism involves two pathways, that is, trans-sulfuration pathway and re-methylation pathway [1]. Homocysteine is metabolized and detoxified by trans-sulfuration to cysteine, via enzymes (cystathionine-b-synthase and cystathionine-c-lyase) dependent on vitamin B 6 as a cofactor [2,3].…”
Section: Introductionmentioning
confidence: 99%